Serous Carcinoma of the Endometrium with Mesonephric-Like Differentiation Initially Misdiagnosed as Uterine Mesonephric-Like Adenocarcinoma: A Case Report with Emphasis on the Immunostaining and the Identification of Splice Site TP53 Mutation - Sangjoon Choi; Yoon Yang Jung; Hyun-Soo Kim (Diagnostics, 2021)
We present herein a rare case of uterine serous carcinoma with mesonephric-like differentiation (SC-MLD) initially misdiagnosed as mesonephric-like adenocarcinoma (MLA). A 51-year-old woman underwent total hysterectomy for a uterine tumor. Histologically, the tumor exhibited various architectures, including papillary, glandular, tubular, cribriform, and cystic. On the basis of this architectural diversity accompanied by intraluminal eosinophilic secretions and intermediate-grade nuclear atypia, the initial diagnosis was MLA. However, the tumor was diffusely and strongly positive for the expression of p16 and negative for the expression of GATA-binding protein 3 (GATA3). Furthermore, we identified a pathogenic tumor protein 53 (TP53) mutation affecting an acceptor splice site in intron 9, despite a wild-type p53 immunostaining pattern. The observations of diffuse and strong p16 expression, lack of GATA3 expression, pathogenic TP53 mutation, and wild-type Kirsten rat sarcoma viral oncogene homolog indicate that this tumor was not an MLA but an SC-MLD. Both uterine SC and MLA can exhibit various histological growth patterns. Our comprehensive clinicopathological and molecular analyses can serve to improve the understanding of this rare condition and help pathologists in making an accurate diagnosis.